A Primary Mesentric Hydatid Cyst- A case report: Hydatid Cyst (Bombay Hospital Journal, 2024)
Hydatid disease is caused by a parasite known as Echinococcus granulosus. Most common sites are the liver and lungs. Primary mesenteric hydatid cyst is very rare1. In this article, the author presents a rare case report of a primary mesenteric hydatid cyst treated laparoscopically. The patient presented to us with a very short duration of history and non specific complaints. As the pre operative investigations were not very conclusive of the diagnosis, we made some differential diagnosis and decided to go ahead with the surgery.
Keywords: Albendazole, Hydatid Cyst, laparoscopy